The Effect of Giving Probiotic Drinks on Reducing Halitosis - Erawati, Suci; Molek; Fitwy Inka Teresha Br. Silaban (HM Publisher, 2022)
Background. Halitosis is a condition in which an unpleasant odor caused by oral microbes comes out of a person's mouth during exhalation, which makes other people feel uncomfortable. Probiotics seek to maintain the homeostasis of bacteria in the gastrointestinal tract to suppress the proliferation of pathogenic bacteria. This study aims to evaluate the potential of probiotics against halitosis as assessed by the levels of volatile sulfur compounds (VSCs). Methods. The design of this study is an experimental study with a pre-post test approach. A total of 30 research subjects with criteria aged 20-28 years with complaints of halitosis seek treatment at the dental and oral polyclinic of Siti Hajar Hospital. Research subjects were asked to rinse their mouth with one of the commercial probiotic drinks already circulating in the market, where previously the levels of volatile sulfur compounds (VSCs) and after rinsing the probiotic drink, the levels of VSCs were measured again. Data analysis was carried out with the help of SPSS version 21 software. A univariate data analysis was carried out to obtain an overview of the distribution of degrees and levels of Volatile, Sulfur Compounds (VSCs) before, and after giving drinks probiotics. Results. The provision of probiotic drinks is sufficient to provide a significant qualitative change effect where there is a change in the degree of halitosis of the research subjects. After consuming probiotics, there was an improvement in the degree of halitosis of the research subjects, whereas there were no more subjects with severe halitosis. Conclusion. Consumption of probiotic drinks can reduce the levels of VSCs in the oral cavity, which indicates the ability of probiotics to reduce halitosis.